Modeling and Validating a SuperDARN Radar's Poynting Flux Profile. Issue 3 (18th March 2022) - Perry, G. W.; Ruzic, K. D.; Sterne, K.; Howarth, A. D.; Yau, A. W.
Abstract: We have developed a model that simulates the Poynting flux profile of the Saskatoon Super Dual Auroral Radar Network (SuperDARN) radar at ionospheric altitudes. The model uses ray tracing software to project the radar system's vacuum Poynting flux profile through the ionosphere, taking into account the influence of the ionospheric medium on the propagation characteristics of the high frequency radio waves. Measurements of the radar's transmissions by the Radio Receiver Instrument (RRI) in low‐Earth orbit are used to validate the model during five experiments which occurred between 4 and 8 August 2017. Comparisons between simulated and measured RRI antenna voltages show good agreement, although there are clear instances in which the model underperforms. Nevertheless, the model demonstrates its utility as a tool for interpreting RRI measurements of SuperDARN radars. The model also helps address a lack of knowledge of a SuperDARN radar's Poynting flux profile at ionospheric altitudes. In particular, we assess the assumption that SuperDARN's scattering volume lies along the great‐circle path of the transmitting beam's bearing. Comparisons between the model and RRI's measurements show that this assumption is reasonable for the five experiments investigated in this work. The model presents a new way of carrying out SuperDARN and high frequency radio science investigations. Plain Language Summary: The Super Dual Auroral Radar Network (SuperDARN) radar system located in Saskatoon, Canada is a powerful tool for studying the high‐latitude ionosphere. Even though the system has been operating nearly continuously since 1993, there is very little understanding of what the radar's Poynting flux profile looks like at ionospheric altitudes where its radar echoes originate. This is simply due to a lack of available measurements. As a result, it is customary to simply assume that the radar's Poynting flux profile at ionospheric altitudes resembles that of its Poynting flux profile in a vacuum projected along great‐circle trajectories up to ionospheric altitudes. This assumption is limited because it does not adequately account for the fact that the radar's Poynting flux profile can be influenced by the ionospheric medium in which it is immersed. In this work, we have developed a model of Saskatoon SuperDARN's Poynting flux profile at ionospheric altitudes which properly accounts for the influence of the ionosphere. Furthermore, we have compared the model's output to several measurements of the Saskatoon radar made by a radio receiver in low‐Earth orbit to validate the model. Our results show that the model is accurate and can be used as a useful tool for studying SuperDARN's Poynting flux profile at ionospheric altitudes. Key Points: The Saskatoon Super Dual Auroral Radar Network radar's Poynting flux profile is modeled in an empirical ionosphere A simulated Poynting flux profile is validated with the Enhanced Polar Outflow Probe Radio Receiver Instrument The Poynting flux model is a useful tool for studying high frequency radio wave propagation